2022
DOI: 10.3390/ijms23052593
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Sub-Acute Toxicity of Formaldehyde Fumes in an In Vitro Human Airway Epithelial Tissue Model

Abstract: Formaldehyde (FA) is an irritating, highly reactive aldehyde that is widely regarded as an asthmagen. In addition to its use in industrial applications and being a product of combustion reaction and endogenous metabolism, FDA-regulated products may contain FA or release FA fumes that present toxicity risks for both patients and healthcare workers. Exposure to airborne FA is associated with nasal neoplastic lesions in both animals and humans. It is classified as a Group 2A carcinogen by International Agency for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…In this study, we showed that repeated exposure to glutaraldehyde (GA) aerosols induced a panel of temporal changes in tissue responses in the ALI cultures. In general, the toxicity responses to GA exposure in the ALI airway cultures are consistent with observations on other aldehydes, i.e., ortho-phthalaldehyde (OPA), formaldehyde, and acrolein, as reported in our previous studies [ 11 , 12 , 13 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, we showed that repeated exposure to glutaraldehyde (GA) aerosols induced a panel of temporal changes in tissue responses in the ALI cultures. In general, the toxicity responses to GA exposure in the ALI airway cultures are consistent with observations on other aldehydes, i.e., ortho-phthalaldehyde (OPA), formaldehyde, and acrolein, as reported in our previous studies [ 11 , 12 , 13 ].…”
Section: Discussionsupporting
confidence: 90%
“…Morphological changes caused by GA aerosols were evaluated at T5 and PT7. Sample preparation and histopathology staining were performed as described previously [ 12 , 13 ]. Hematoxylin and eosin (H&E) staining was conducted using a Leica Autostainer (Buffalo Grove, IL, USA); histopathologic changes were evaluated and scored by a board-certified pathologist.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the FDA’s recommendations, various in vitro samples were declared as qualified alternative methods that incorporate the 3Rs, such as but not limited to organs-on-a-chip. For example, lung microphysiological systems were used to evaluate the toxicity induced by subacute exposures to formaldehyde fumes at different concentrations . In another example, liver microphysiological systems were used to study drugs with high liver toxicity to demonstrate effectiveness and to suggest reduced risk .…”
Section: Introductionmentioning
confidence: 99%
“…Formaldehyde (FA), with the chemical formula CH 2 O, is a colorless, strongly irritating gas that is widely found in nature, industrial production and consumer products [7,8]. FA is classi ed as a Group 1 carcinogen by International Agency for Research on Cancer (IARC) and a known carcinogen by NTP [9,10]. It has been reported that long-term exposure to FA exceeding the national standard concentration has a variety of toxic effects on the nasopharynx, lung, brain, skin, as well as on the hematopoietic organs bone marrow (BM) and spleen [11], even leading to cancer [12,13].…”
Section: Introductionmentioning
confidence: 99%